LINGUACULTURAL DIFFERENCES IN THE CONCEPT OF MAN AND WOMAN IN ENGLISH AND KARAKALPAK LANGUAGES: LINGUACULTURAL DIFFERENCES IN THE CONCEPT OF MAN AND WOMAN IN ENGLISH AND KARAKALPAK LANGUAGES - Amangeldieva, Alfiya (Журнал иностранных языков и лингвистики, 2025)
Language serves not only as a communication tool but also as a cultural mirror, revealing the values, beliefs, and societal structures of the people who speak it. The way we talk about gender – what it means to be a "man" or a "woman" – is deeply rooted in the cultural fabric of our communities. The differences in how gender concepts are linguistically represented across languages shed light on how various societies perceive gender roles and identities.